Pathogenic variants of ornithine transcarbamylase deficiency: Nation-wide study in Japan and literature review - Kido, Jun; Sugawara, Keishin; Sawada, Takaaki; Matsumoto, Shirou; Nakamura, Kimitoshi (Frontiers in Genetics, 2022)
Ornithine transcarbamylase deficiency (OTCD) is an X-linked disorder. Several male patients with OTCD suffer from severe hyperammonemic crisis in the neonatal period, whereas others develop late-onset manifestations, including hyperammonemic coma. Females with heterozygous pathogenic variants in the OTC gene may develop a variety of clinical manifestations, ranging from asymptomatic conditions to severe hyperammonemic attacks, owing to skewed lyonization. We reported the variants of CPS1, ASS, ASL and OTC detected in the patients with urea cycle disorders through a nation-wide survey in Japan. In this study, we updated the variant data of OTC in Japanese patients and acquired information regarding genetic variants of OTC from patients with OTCD through an extensive literature review. The 523 variants included 386 substitution (330 missense, 53 nonsense, and 3 silent), eight deletion, two duplication, one deletion-insertion, 55 frame shift, two extension, and 69 no category (1 regulatory and 68 splice site error) mutations. There was a significant genotype-phenotype correlation in the male OTCD patients because the deactivation level of OTC significantly depends on the pathogenic OTC variants. In conclusion, genetic information about OTC may help to predict long-term outcomes and determine specific treatment strategies, such as liver transplantation, in patients with OTCD.